Immune and ionic mechanisms mediating the effect of dexamethasone in severe COVID-19 - Chimote, Ameet A.; Alshwimi, Abdulaziz O.; Chirra, Martina; Gawali, Vaibhavkumar S.; Powers-Fletcher, Margaret V.; Hudock, Kristin M.; Conforti, Laura (Frontiers in Immunology, 2023)
Introduction Severe COVID-19 is characterized by cytokine storm, an excessive production of proinflammatory cytokines that contributes to acute lung damage and death. Dexamethasone is routinely used to treat severe COVID-19 and has been shown to reduce patient mortality. However, the mechanisms underlying the beneficial effects of dexamethasone are poorly understood. Methods We conducted transcriptomic analysis of peripheral blood mononuclear cells (PBMCs) from COVID-19 patients with mild disease, and patients with severe COVID-19 with and without dexamethasone treatment. We then treated healthy donor PBMCs in vitro with dexamethasone and investigated the effects of dexamethasone treatment ion channel abundance (by RT-qPCR and flow cytometry) and function (by electrophysiology, Ca2+ influx measurements and cytokine release) in T cells. Results We observed that dexamethasone treatment in severe COVID-19 inhibited pro-inflammatory and immune exhaustion pathways, circulating cytotoxic and Th1 cells, interferon (IFN) signaling, genes involved in cytokine storm, and Ca2+ signaling. Ca2+ influx is regulated by Kv1.3 potassium channels, but their role in COVID-19 pathogenesis remains elusive. Kv1.3 mRNA was increased in PBMCs of severe COVID-19 patients, and was significantly reduced in the dexamethasone-treated group. In agreement with these findings, in vitro treatment of healthy donor PBMCs with dexamethasone reduced Kv1.3 abundance in T cells and CD56dimNK cells. Furthermore, functional studies showed that dexamethasone treatment significantly reduced Kv1.3 activity, Ca2+ influx and IFN-g production in T cells. Conclusion Our findings suggest that dexamethasone attenuates inflammatory cytokine release via Kv1.3 suppression, and this mechanism contributes to dexamethasone-mediated immunosuppression in severe COVID-19.